Circ‐U2AF1 promotes human glioma via derepressing neuro‐oncological ventral antigen 2 by sponging hsa‐miR‐7‐5p. Issue 6 (20th October 2018) - Li, Guoxiong; Huang, Min; Cai, Yingqian; Yang, Yuantao; Sun, Xinlin; Ke, Yiquan
Abstract: The prognosis for human glioma, a malignant tumor of the central nervous system, is poor due to its rapid growth, genetic heterogeneity, and inadequate understanding of its underlying molecular mechanisms. Circular RNAs composed of exonic sequences, represent an understudied form of noncoding RNAs (ncRNAs) that was discovered more than a decade ago, function as microRNA sponges. We aimed to assess the relationship between circ‐U2AF1 (CircRNA ID: hsa_circ_0061868) and hsa‐mir‐7‐5p and examine their effects on proliferation, apoptosis, and the metastatic phenotype of glioma cells regulated by neuro‐oncological ventral antigen 2 (NOVA2). We found that the expression levels of circ‐U2AF1 and NOVA2 were upregulated, while hsa‐miR‐7‐5p was downregulated in human glioma tissues and glioma cell lines. Our data and bioinformatic analysis indicated the association of these molecules with glioma grade, a positive correlation between circ‐U2AF1 and NOVA2 expression levels and a negative correlation of hsa‐miR‐7‐5p with both circ‐U2AF1 and NOVA2, respectively. In addition, silencing of circ‐U2AF1 expression resulted in increased hsa‐miR‐7‐5p expression and decreased NOVA2 expression both in vitro and in vivo. Luciferase assay confirmed hsa‐miR‐7‐5p as a direct target of circ‐U2AF1 and NOVA2 as a direct target of hsa‐miR‐7‐5p. Functionally, silencing of circ‐U2AF1 inhibits glioma development by repressing NOVA2 via upregulating hsa‐miR‐7‐5p both in vitro and in vivo. Thus, we assumed that circ‐U2AF1 promotes glioma malignancy via derepressing NOVA2 by sponging hsa‐miR‐7‐5p. Taken together, we suggest that circ‐U2AF1 can be a prognostic biomarker and the circ‐U2AF1/hsa‐miR‐7‐5p/NOVA2 regulatory pathway may be a novel therapeutic target for treating gliomas. Abstract : We suggest that circ‐U2AF1 can be a prognostic biomarker and the circ‐U2AF1/hsa‐miR‐7‐5p/NOVA2 regulatory pathway may be a novel therapeutic target for treating gliomas.